2012
DOI: 10.1007/s12603-011-0098-1
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between body mass index, calf circumference, arm circumference, habitual energy intake and the MNA in hospitalized elderly

Abstract: The best parameters to determine nutritional risk in relation to the MNA were AC, BMI and CC. However, these nutritional assessment parameters should be used to replace the MNA for the assessment of hospitalized elderly patients with their current cut-off points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…This supports a recently suggested cutoff of 26.2 cm to optimize the sensitivity and specificity of this measure. 26 Completion rates were high for circumference measures, although BMI completion rates in this study were low because of difficulties obtaining admission weights for a limited number of participants. Data from this study suggest that reported height and weight to determine BMI should be cautiously interpreted in this population in the setting of high levels of cognitive impairment and limited ability to obtain collateral data from third parties.…”
Section: E43 Unspecified Severe Protein-energy Malnutritionmentioning
confidence: 68%
“…This supports a recently suggested cutoff of 26.2 cm to optimize the sensitivity and specificity of this measure. 26 Completion rates were high for circumference measures, although BMI completion rates in this study were low because of difficulties obtaining admission weights for a limited number of participants. Data from this study suggest that reported height and weight to determine BMI should be cautiously interpreted in this population in the setting of high levels of cognitive impairment and limited ability to obtain collateral data from third parties.…”
Section: E43 Unspecified Severe Protein-energy Malnutritionmentioning
confidence: 68%
“…Individual characteristics, such as mood, behaviour, communication, hearing and sight problems, were included as parts of multidimensional assessment scales. In particular, a modified version of the Barthel Index was used to measure the subjects’ performance in activities of daily life, where a score of 100 indicates “complete dependency” [ 34 , 35 ]; the Pfeiffer test was used to assess cognitive deficits [ 36 ]; the Eating Behaviour Scale to measure patients’ functional ability during eating [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Scores were allocated for recent weight loss (1 = 0.5-5, 2 = 5-10, 3 = 10-15, 4 = >15 kg over 6 months, 2 = unsure) and eating poorly because of a reduced appetite (yes = 1) with a MST score 2 or more indicating risk of malnutrition in accordance with the criteria described by Ferguson et al (1999) Body mass index In line with the British Association for Parenteral and Enteral Nutrition (BAPEN) criteria, patient-reported height was recorded if considered as reliable and accurate; alternately, calculated height was obtained by a trained nutrition assistant or dietitian via ulna measurements using the methodology described by the BAPEN (Malnutrition Advisory Group, 2003). The BMI cut-off value for nutritional risk was therefore set at <22.0 kg m -2 in line with other studies investigating identification and diagnosis of malnutrition in elderly patients (Miller et al, 2009;Aparecida Leandro-Merhi et al, 2012). In the absence of a recorded weight, reported weights were used if considered reliable and accurate in accordance with the BAPEN guidelines (Malnutrition Advisory Group, 2003).…”
Section: Malnutrition Screening Toolmentioning
confidence: 99%
“…However, adopting a nutrition screening cut-off at the same level as that broadly used for malnutrition diagnosis may lead to the under-identification of patients at risk of malnutrition, particularly in elderly or multi-morbid populations (Chapman, 2011). The BMI cut-off value for nutritional risk was therefore set at <22.0 kg m -2 in line with other studies investigating identification and diagnosis of malnutrition in elderly patients (Miller et al, 2009;Aparecida Leandro-Merhi et al, 2012).…”
Section: Malnutrition Screening Toolmentioning
confidence: 99%